Space Tourism Activities Overview of International Law - Ayu Dewily, Ratih Dara; Faculty Of Law Universitas 17 Agustus 1945 Surabaya (Journal of International Trade, Logistics and Law, 2021)
Space tourism activity is one example of commercialization activity in space.  currently this activity is still in a development session which is better for the future. Thus, the description of space tourism activities is a matter that deserves to be known from history to all of its details and seen from the growth and difficulty in increasing space tourism activities, of course it must be supported by laws or regulations governing space. Not only that, so far there have been space tourists as well as potential space tourists who have departed for this tourism activity.  Thus, this space tourism activity is intended to be an activity that can be tried on a regular basis in the future, so that international and national legal arrangements must be well organized, fair and responsible and with regard to the rapid growth of this activity, it’s appropriate for those who participating or having an interest in this activity must be more open in the growth of the activities they are carrying out, so that steps can be taken quickly, it seems like for example, to quickly formulate and ratify a space agreement related to space tourism, protection of parties who participate in activities it's kind of like the private industry. The research objectives, namely